Enhanced stability and oxidation resistance of Acer truncatum Bunge seed oil Pickering emulsion using rice bran protein modified by phytic acid - Jianjun Huang; Ruyi Sha; Jing Dai; Zhenzhen Wang; Min Cai; Xianxiu Li; Jianwei Mao (Food Chemistry: X)
The potential applications of Acer truncatum Bunge seed oil in the food and medical industries are constrained by its susceptible fatty acid composition, which is prone to oxidation. In this study, rice bran protein (RBP) was employed as an emulsifier for the fabrication of Acer truncatum Bunge seed oil Pickering emulsion. The impact of antioxidant-phytic acid (PA) on the stability of Pickering emulsion and the underlying mechanisms were further investigated. The findings indicate that PA is capable of interacting with RBP, resulting in a change in its spatial conformation. When the PA concentration was increased from 0 to 0.01 % (w/v), the number of α-helices of RBP-PA particles decreased by 5 %, the number of β-sheets and interfacial adsorbed proteins increased by 2.89 % and 39.83 %. Additionally, and the surface hydrophobicity was increased from 50 ± 3.63 (a.u.) to 429 ± 20.03 (a.u.), and the range of the particle size distribution was reduced from 1 to 10 μm to 295–459 nm, and the zeta potential decreased from −23.43 ± 0.46 mV to −53.4 ± 1.35 mV. The Acer truncatum Bunge seed oil Pickering emulsion, containing 0.01 % PA, exhibits favourable static stability and lipid oxidative stability, allowing for storage at room temperature for a period exceeding 50 days.